Mejoramiento de un equipo para el drenaje de líquidos en tanques cónicos mediante la implementación de un sistema automatizado - Estrella Guerra, Naomi Gianella (2023)
The objectify general of the present investigation it was: accomplishing the improvement of the team for the liquids drain in conical tanks, by means of the development of a system automated; being deduced firstly the intervening mathematical model which determined the passage of time to drain a certain quantity of liquid volume in conical tanks itself, Being applicable ad hoc the equation of continuity and the general equation of energy. From now on, the frame-up of the automated system came true, which was shaped by the following components: A programmable relay, the software Zelio Soft2 V5.4.2, the interface of communication, a valve solenoid, a red push-button NC, a green push-button NA, an indicating rookie pilot and a thermic key with its bipolar plug. At last, when moved in the aforementioned system automated in the conical tank, eight (8) performance testings, in the same ones that were determined the passage of time programmed in the automated system came true, which worked out: 58.6 s, 56.2 s, 59.1 s, 50.6 s, 49.0 s, 67.4 s, 59.5 s and 54.5 s, respectively. Also, they obtained the following results, regarding the maximum percentage of error, of the final level of liquid, of the final volume of liquid and of the draining volume, which were: 1.27 %, 3.85 % and 2.02 %, respectively, trying on this way, that to apply said mathematical model they obtain to the 95 % results with a bigger reliability. The present investigation this way is concluded, coming true with the objectify general al and trying on his general hypothesis.